The direct strength method for combined bending and web crippling of second-generation trapezoidal steel sheeting. (October 2021) - Willems, D.W.C.; Hofmeyer, H.; Snijder, H.H.; Schafer, B.W.
Abstract: Second-generation trapezoidal sheeting, characterised by longitudinal stiffeners in webs and flanges, is loaded near a support by a concentrated force and a bending moment. Currently, design codes predict related failure by: (a) determining the ultimate bending moment via the effective width approach or the Direct Strength Method (DSM); (b) finding the web crippling load via a curve-fitted formula; and (c) using an interaction rule to take into account the load combination. However, the effective width approach is quite complex to use for many longitudinal stiffeners, and the accuracy of the design codes is subject to improvement. Moreover, nowadays the DSM provides a consistent and well-established method to predict ultimate loads for cold-formed steel structures. Therefore, in this paper the application of the DSM for combined bending and web crippling of second-generation sheeting is investigated. First, to create a set of numerical experiments, an internationally representative set of second-generation trapezoidal sheeting types is found, and these types are used to design numerical three-point bending experiments with relevant span lengths and load bearing plate widths. Then, finite element models are developed and verified, and used to predict the buckling, yield, and ultimate loads for the set of numerical experiments. Additionally, all simulations are also carried out for pure bending, and (Interior One Flange) IOF and (Interior Two Flange) ITF web crippling cases. With the resulting data, an explicit DSM approach is developed, fitted to the data of the three-point bending simulations, which predicts the ultimate load for combined actions directly. Hereafter, also an interaction DSM approach is studied, which first predicts the ultimate bending moment by the DSM (by fitting the pure bending simulations), then the web crippling load by the DSM (by fitting either the IOF or ITF simulations), and then uses a classic interaction rule for the load combination. The explicit and implicit DSM approaches perform equally well, with a Coefficient of Variation (CoV) equal to 0.13. As most commercially available sheeting has been incorporated, and the DSM approaches allow for sections with an arbitrarily number of stiffeners in the web (different from the current design codes), it is recommended to include the DSM in future code revisions. The interaction DSM approach resembles the current design rules most and may therefore be preferred; however, the explicit approach is more direct and certainly deserves consideration too. Highlights: Currently available second-generation sheeting organised and studied. FE simulations provide DSM data for Eigenvalues, yield load, ultimate load. No need to model stiffener corners. Both explicit and implicit DSM show COV = 0.13. TF Eigenvalues or yield loads do not improve web crippling results.